ANALYSIS OF THE EFECTS OF AN AC ELECTROMAGNETIC FIELD EXPOSURE IN MICROCIRCULATION OF HUMANS BY USING A 2D LASER SPECKLE FLOWMETRY - Azmi, N.I.F.; Okano, H.; Takahashi, R.; Kondo, T.; Ishiwatari, H.; Watanuki, K. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
To date, there are only a few reports evaluating non-thermal alternating current electromagnetic exposure for medical therapeutic applications. Here, we analyzed the acute effects of hand and forearm exposure to a 50 Hz electromagnetic field (EMF; peak magnetic flux density Bmax 180 mT, Brms 127 mT, 15-min duration of exposure) on cutaneous microcirculation in 11 healthy human subjects (10 males and 1 female, age betwen 22-57 years). The blood flow volume values in the back of the hand were monitored and analyzed using a 2D laser speckle flowmetry. Regional blood flow volume values in sham control exposure were significantly reduced from baseline values during resting conditions. In contrast, the EMF exposure did not significantly decreased the blood flow volume from the baseline values during and after the EMF exposure period. There were significant differences between the EMF and sham exposure groups. Therefore, the EMF exposure significantly prevented the reduction of blood flow volume. Thus, the EMF could improve blood flow volume in cutaneous tissue under ischemic conditions. These findings imply that the physiological role of an EMF-enhanced blood circulation might help eliminate the metabolic waste products including endogenous pain producing substances inducing muscle hardness and pain.